2023
DOI: 10.1097/md.0000000000032909
|View full text |Cite
|
Sign up to set email alerts
|

Factors predictive of functional outcomes and quality of life in patients with fragility hip fracture: A retrospective cohort study

Abstract: To determine the predictors of functional outcomes and quality of life (QoL) of patients who were surgically treated for fragility hip fracture. This was a retrospective cohort study performed in the 3 tertiary rehabilitation facilities. A total of 165 patients who had undergone surgery for fragility hip fracture were followed up to 6 months postoperatively. The factors expected to be related to the functional outcomes and QoL at 6 months post-surgery were as follows: baseline demographics, fracture site, oper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 96 publications
1
2
1
Order By: Relevance
“…Comorbidity also did not predict functional ability two weeks post-hospital discharge. Our findings differ from prior studies [26,38,39], which have indicated that comorbidities affect functional recovery. Additionally, the findings of this study revealed that severe health conditions-those with an ASA classification of 3-4-did not predict good functional ability two weeks postdischarge when compared to the other classifications, which differ from the findings of previous studies [40].…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Comorbidity also did not predict functional ability two weeks post-hospital discharge. Our findings differ from prior studies [26,38,39], which have indicated that comorbidities affect functional recovery. Additionally, the findings of this study revealed that severe health conditions-those with an ASA classification of 3-4-did not predict good functional ability two weeks postdischarge when compared to the other classifications, which differ from the findings of previous studies [40].…”
Section: Discussioncontrasting
confidence: 99%
“…This study's findings revealed that internal fixation procedures of the hip were a significant predictor of poor postoperative functional ability immediately after hospital discharge. These results are consistent with previous studies [26,29]. However, internal fixation requires a longer time for the bone to heal, meaning that it may be less likely for patients to regain normal functional ability when followed up at 12 months [15].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Accordingly, HF has been so far acknowledged as one of the leading causes of disability and mortality in this age group, and its related costs have been a global economic burden. It is notable that fewer than 40–60% of HF survivors regain their pre-fracture mobility status [ 2 ]. Furthermore, this condition is closely associated with multiple deficiencies in activities of daily living (ADLs), which subsequently result in loss of independence and low self-esteem.…”
Section: Introductionmentioning
confidence: 99%